Tools and Strategies for Long-Read Sequencing and De Novo Assembly of Plant Genomes. (August 2019) - Jung, Hyungtaek; Winefield, Christopher; Bombarely, Aureliano; Prentis, Peter; Waterhouse, Peter
Abstract : The commercial release of third-generation sequencing technologies (TGSTs), giving long and ultra-long sequencing reads, has stimulated the development of new tools for assembling highly contiguous genome sequences with unprecedented accuracy across complex repeat regions. We survey here a wide range of emerging sequencing platforms and analytical tools for de novo assembly, provide background information for each of their steps, and discuss the spectrum of available options. Our decision tree recommends workflows for the generation of a high-quality genome assembly when used in combination with the specific needs and resources of a project. Highlights: Tumbling sequencing costs, improvements in bioinformatic pipelines, and increased access to high-performance computing capabilities have resulted in a perfect storm where nonspecialist genomics research groups are able to access, deploy, and generate de novo genome sequences in nonmodel plant systems. However, generating a high-quality assembly for many plant species still presents significant challenges owing to genome size, complexity, and experimental and computational design. Selecting the most appropriate sequencing and software platforms for a new genome project can be confusing and daunting because of the wide spectrum of available options and the performance quality of specific tools in different contexts.